2009
DOI: 10.3998/ark.5550190.0010.a29
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis, antibacterial activity against Bordetella bronchiseptica of a library of 3΄-hydroxyaryl and heteroaryl chalcones and molecular descriptors-based SAR

Abstract: Microwave assisted synthesis of 33 membered parallel library of aryl-and heteroaryl chalcones was carried out by reaction of 3-hydroxyacetophenone with different substituted aryl-and heteroaryl aldehydes under Claisen-Schmidt conditions. The synthesized chalcones are significantly active against Bordetella bronchiseptica (ATCC 4617), gram negative respiratory pathogen that infects wide range of animals and human using cefixime as standard antibiotic as control. Tested compounds show moderate inhibitory activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…(3 -Hydroxyphenyl)-3-(2-chlorophenyl)-2propen-1-one (11m), 1-(3 -Hydroxyphenyl)-3-(3-chlorophenyl)-2-propen-1-one (11n), 1-(3 -Hydroxyphenyl)-3-(4-chlorophenyl)-2-propen-1-one (11o) and 1-(3 -Hydroxyphenyl)-2-(3bromophenyl)-2-propen-1-one (11p) with MIC value of ≥0.2 mg/mL showed better antibacterial action than those derivatives which had polar hydroxy and methoxy groups such as 1-(3 -Hydroxyphenyl)-3-(2-hydroxyphenyl)-2-propen-1-one (11b), 1-(3 -Hydroxyphenyl)-3-(3-hydroxyphenyl)-2-propen-1-one (11c), 1-(3 -Hydroxyphenyl)-3-(4-hydroxyphenyl)-2-propen-1-one (11d), 1-(3 -Hydroxyphenyl)-3-(2-methoxyphenyl)-2-propen-1-one (11e), 1-(3 -Hydroxyphenyl)-3-(3-methoxyphenyl)-2-propen-1-one (11f), 1-(3 -Hydroxyphenyl)-3-(4-methoxyphenyl)-2-propen-1-one (11g), 1-(3 -Hydroxyphenyl)-3-(3,4-dimethoxyphenyl)-2-propen-1-one (11h), 1-(3 -Hydroxyphenyl)-3-(4-hydroxy,3-methoxyphenyl)-2-propen-1one (11i), and 1-(3 -Hydroxyphenyl)-3-(2-methyl-3,5-dimethoxyphenyl)-2-propen-1-one(11w) (MIC > 0.6 mg/mL). Furthermore, some polar compounds, such as 11h,i,w, displayed no activity[98].…”
mentioning
confidence: 98%
“…(3 -Hydroxyphenyl)-3-(2-chlorophenyl)-2propen-1-one (11m), 1-(3 -Hydroxyphenyl)-3-(3-chlorophenyl)-2-propen-1-one (11n), 1-(3 -Hydroxyphenyl)-3-(4-chlorophenyl)-2-propen-1-one (11o) and 1-(3 -Hydroxyphenyl)-2-(3bromophenyl)-2-propen-1-one (11p) with MIC value of ≥0.2 mg/mL showed better antibacterial action than those derivatives which had polar hydroxy and methoxy groups such as 1-(3 -Hydroxyphenyl)-3-(2-hydroxyphenyl)-2-propen-1-one (11b), 1-(3 -Hydroxyphenyl)-3-(3-hydroxyphenyl)-2-propen-1-one (11c), 1-(3 -Hydroxyphenyl)-3-(4-hydroxyphenyl)-2-propen-1-one (11d), 1-(3 -Hydroxyphenyl)-3-(2-methoxyphenyl)-2-propen-1-one (11e), 1-(3 -Hydroxyphenyl)-3-(3-methoxyphenyl)-2-propen-1-one (11f), 1-(3 -Hydroxyphenyl)-3-(4-methoxyphenyl)-2-propen-1-one (11g), 1-(3 -Hydroxyphenyl)-3-(3,4-dimethoxyphenyl)-2-propen-1-one (11h), 1-(3 -Hydroxyphenyl)-3-(4-hydroxy,3-methoxyphenyl)-2-propen-1one (11i), and 1-(3 -Hydroxyphenyl)-3-(2-methyl-3,5-dimethoxyphenyl)-2-propen-1-one(11w) (MIC > 0.6 mg/mL). Furthermore, some polar compounds, such as 11h,i,w, displayed no activity[98].…”
mentioning
confidence: 98%
“…and antimicrobial activity studies of compound T10 against Staphylococcus aureus by Talia et al were mentioned [38] . Besides, enzyme and cytotoxic activity studies of compounds T11 and T13 [39] and antimicrobial activity studies of T12 were reported [40] . Fandaklı et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, biological activities of these analyzed compounds T1-2, T4-8, and T10-20 were reported in the literature, [30,[33][34][35][36][37][38][39][40][41][42][43][44][45] and the synthesis and activities of T3 and T9 compounds were performed for the first time in this study. Other studies were shown antioxidant and cytotoxic activity studies of T5 [34,35] and antibacterial and anti-inflammatory activity studies of T6 and T7 compounds.…”
Section: Evaluation Of Antimicrobial Activities Of Compounds T1-20mentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 3a–g were synthesized by the method described by Narender et al 21 NMR, MS, IR data, and melting point of the known compounds were consistent with those reported previously. 2228…”
Section: Methodsmentioning
confidence: 99%